2012
DOI: 10.1523/jneurosci.1912-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Is Essential for Survival of Postmitotic Neurons

Abstract: The retinoblastoma protein (Rb) family members are essential regulators of cell cycle progression, principally through regulation of the E2f transcription factors. Growing evidence indicates that abnormal cell cycle signals can participate in neuronal death. In this regard, the role of Rb (p105) itself has been controversial. Germline Rb deletion leads to massive neuronal loss, but initial reports argue that death is non-cell autonomous. To more definitively resolve this question, we generated acute murine kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 32 publications
7
51
0
Order By: Relevance
“…The differential regulation of proapoptotic versus cell cycle-related targets may be specific to neurons, in line with a previous report. 47 On the whole, these data show that Notch signaling positively regulates the Akt/Ccnd1 axis leading to cell cycle-related gene expression (Figure 5c). …”
Section: Discussionmentioning
confidence: 79%
“…The differential regulation of proapoptotic versus cell cycle-related targets may be specific to neurons, in line with a previous report. 47 On the whole, these data show that Notch signaling positively regulates the Akt/Ccnd1 axis leading to cell cycle-related gene expression (Figure 5c). …”
Section: Discussionmentioning
confidence: 79%
“…The massive neuronal loss in developing nervous system with Rb germline loss-of-function mutations can be explained by placental formation defects (de Bruin et al 2003). However, acute murine knockout models of Rb in terminally differentiated neurons in vitro and in vivo reported that acute inactivation of Rb in postmitotic neurons results in ectopic cell cycle protein expression and neuronal loss without concurrent induction of classical E2f-mediated apoptotic genes, such as Apaf1 (Andrusiak et al 2012). These results suggest that terminally differentiated neurons require Rb for continuous cell cycle repression and survival.…”
Section: Rb Functionsmentioning
confidence: 99%
“…Differentiating cortical neurons survive and proliferate when Rb is conditionally deleted before the start of cortical development (Ferguson et al, 2002;MacPherson et al, 2003). In adults, the acute inactivation of Rb in mature cortical neurons results in neuronal loss, demonstrating that Rb is essential for the survival of mature cortical neurons (Andrusiak et al, 2012). Although these studies clearly demonstrated that Rb-deficient differentiating cortical neurons, but not adult mature cortical neurons, escape cell death after S-phase re-entry, acute Rb inactivation in cortical differentiating neurons is inevitable for elucidating whether differentiating cortical neurons retain their proliferative potency after neurogenesis or whether the Rb-deficient primordium of the cerebral cortex generates proliferative differentiating neurons because of the context-specific roles of Rb.…”
Section: Introductionmentioning
confidence: 99%